Life cycle model of medical project - Рач, Валентин Анатольевич; Масауд, Султан (Eastern-European Journal of Enterprise Technologies, 2012)
The life cycle graphic model of medical project is developed. Peculiar phases, stages are set and polystrategic essence of the curative project is exposed